Ethics in Transaction Cost Economics - Veiga, M. R. da; Major, M. (SESRR 2019 book of abstracts, 2019)
This paper provides Aristotelian virtue ethics analysis of decisions regarding the UN internal oversight governance structures focused on Transaction Cost Economics (TCE) theory. We explore “probity” and “independence” transactions’ attributes through historical narrative case based research to answer to the question – Why consecutive decisions to strengthen internal oversight structures did not relieve “probity” hazards? Our analysis shows that, at the UN, increased oversight governance structures, i.e. incentives, did not relieve probity/ethics hazards as predicted in TCE (Williamson, 1999). It follows that executive powers’ as well as overseers’ systematically trumpeted the UN “rules of the game”, breaching probity/ethics, disregarding the oversight independence prerogative as well as the UN Charter failing to contribute to the “common good” and to protect the UN mission. It also follows that, as it stands by now, the internal oversight mechanism design is deffective insofar as the UN Charter, positions the Secretary-General in constant conflict of interest empowering he/she with both executive and judiciary powers. We apply Williamson’s Public and Private Bureaucracies TCE for the first time. It results that it should be modified to include “virtue ethics” behavioral assumption as a transaction costs’ reduction device and explanatory framework for ethical failures abandoning the opportunism behavioral assumption.